Flexible dispersal dimorphism in zooplankton resting eggs: an example of repeated phenotypic coin flipping?. (10th October 2013) - Pinceel, Tom; Vanschoenwinkel, Bram; Brendonck, Luc
<x xml:space="preserve">Abstract</x> Theory predicts that spatio‐temporal variation in habitat suitability will promote selection for dispersal. In addition to movement in space, dispersal gains an extra dimension in freshwater zooplankton because resting eggs can disperse in time as well, via dormancy. Potential trade‐offs between both strategies, however, remain largely unexplored. Using a temporary pool fairy shrimp population as a model, we tested for consistent differences in buoyancy among resting eggs during consecutive inundations in a standardized laboratory experiment and explored a potential trade‐off between dispersal (floaters versus sinkers) and dormancy (high versus low hatching fractions). Although discrete dispersal morphs were present, this trait was not fixed. Irrespective of their dispersal phenotype during previous inundations, floating eggs hatched more frequently than sinking eggs. Egg morphology did not affect buoyancy and, between inundations, approximately half of the eggs changed their dispersal phenotype. Although this mechanism has affinities with conservative bet hedging and adaptive coin flipping, it is unique because the dispersal phenotype can switch at the onset of each inundation. Despite possible selection against dispersal at the population level, such a strategy ensures variation in dispersal ability at any moment and could promote population persistence in a metapopulation context. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 749–756.